Navigating the post-pandemic era: A study on the digital transformation of SMEs in Bohol, Philippines - Dela Cruz, Allyssa Julia Denise S. (Animo Repository, 2023)
The COVID-19 pandemic had an unprecedented impact on society, especially on various industries and businesses. In the Philippines, social distancing and lockdown measures forced multiple businesses to cease their operations. Despite this, several businesses were able to adapt and overcome such restrictions, with many undergoing digitalization, and with some even flourishing because of said efforts. Having said that, the study investigates the impact of digital technology, digital competitiveness, digital consumer behavior, and organizational culture on the digital transformation efforts of small and medium enterprises (SMEs) in Bohol, Philippines. Digital technology refers to any digital hardware or software that a business may use in its operations, while digital competitiveness is a business’s ability to use such technology to differentiate itself from its competitors. Digital consumer behavior, meanwhile, is the impact of digital technology and techniques on consumer behavior, while organizational culture refers to the shared beliefs and ideals of an organization’s members. With that, individuals who work for or own businesses in Bohol were surveyed and interviewed regarding the impact of the aforementioned variables on their business’s digital transformation efforts. The obtained data were then analyzed using descriptive statistics, and the Pearson correlation coefficient of each variable was calculated and subsequently analyzed. The quantitative data also underwent regression and moderation analysis, while the qualitative data was assessed using both the deductive approach and pattern matching. Ultimately, it was found that digital technology, digital competitiveness, digital consumer behavior, and organizational culture all significantly impact such efforts. Although, the results also show that organizational culture does not possess a moderating effect on the aforementioned variables’ impact on digital transformation. In conclusion, several factors impact a business’s digital transformation efforts and businesses must consider and invest in each of said factors, so that they may fully realize the potential of digital techniques and strategies. Keywords: digital transformation; post-pandemic; small and medium enterprises; digitalization; digital strategies